Polymer derived ceramics with β-eucryptite fillers: A novel processing route to negative and near zero expansion materials. Issue 5 (1st April 2017) - Fedorova, Anna; Hourlier, Djamila; Scheffler, Michael
Abstract: A polymer derived ceramic with near-zero or negative thermal expansion was manufactured from a powder mixture consisting of β-eucryptite fillers having a negative thermal expansion, and a polymethylsilsesquioxane preceramic polymer. The composite starting material was manufactured by ball-milling and warm-pressing and pyrolysis in inert atmosphere. The thermal expansion behavior of the composite material was controlled via the filler volume fraction and via the pyrolysis temperature. An influence of the filler material on the pyrolysis process was found. Graphical abstract: